The beneficial effect of chronic muscular exercise on muscle fragility is increased by Prox1 gene transfer in dystrophic mdx muscle. - Alexandra Monceau; Clément Delacroix; Mégane Lemaitre; Gaelle Revet; Denis Furling; Onnik Agbulut; Arnaud Klein; Arnaud Ferry (PLoS ONE, 2022)
Purpose Greater muscle fragility is thought to cause the exhaustion of the muscle stem cells during successive degeneration/repair cycles, leading to muscle wasting and weakness in Duchenne muscular dystrophy. Chronic voluntary exercise can partially reduce the susceptibility to contraction induced-muscle damage, i.e., muscle fragility, as shown by a reduced immediate maximal force drop following lengthening contractions, in the dystrophic mdx mice. Here, we studied the effect of Prospero-related homeobox factor 1 gene (Prox1) transfer (overexpression) using an AAV on fragility in chronically exercised mdx mice, because Prox1 promotes slower type fibres in healthy mice and slower fibres are less fragile in mdx muscle. Methods Both tibialis anterior muscles of the same mdx mouse received the transfer of Prox1 and PBS and the mice performed voluntary running into a wheel during 1 month. We also performed Prox1 transfer in sedentary mdx mice. In situ maximal force production of the muscle in response to nerve stimulation was assessed before, during and after 10 lengthening contractions. Molecular muscle parameters were also evaluated. Results Interestingly, Prox1 transfer reduced the isometric force drop following lengthening contractions in exercised mdx mice (p < 0.05 to 0.01), but not in sedentary mdx mice. It also increased the muscle expression of Myh7 (p < 0.001), MHC-2x (p < 0.01) and Trpc1 (p < 0.01), whereas it reduced that one of Myh4 (p < 0.001) and MHC-2b (p < 0.01) in exercised mdx mice. Moreover, Prox1 transfer decreased the absolute maximal isometric force (p < 0.01), but not the specific maximal isometric force, before lengthening contraction in exercised (p < 0.01) and sedentary mdx mice. Conclusion Our results indicate that Prox1 transfer increased the beneficial effect of chronic exercise on muscle fragility in mdx mice, but reduced absolute maximal force. Thus, the potential clinical benefit of the transfer of Prox1 into exercised dystrophic muscle can merit further investigation.